perancangan sistem informasi akuntansi pendapatan penjualan menggunakan metode cash basis di warung 3 saudara - Juneri, Gladio; Marfalino, Hari; Trisna, Novi (Riset Sinergi Indonesia, 2023)
The development of information technology in the current era is growing rapidly, along with the increasing human need fortechnology and information. Accounting information sistem is a functional information system and underlies other functionalinformation systems such as financial information, other information systems that require financial data from the systemaccountancy. Financial accounting is accounting with a primary purpose produce financial information for the benefit of outside parties, in question outsiders are parties outside the company's management, the company is still using a manual system or recording into a book, so often there was an error in calculating finance at warung 3 brothers.So this study aims to design a cashier system that is used for recording sales reports, assist employees and consumers intransaction services so as to assist employees in carrying out financial transaction processes, the process of financialtransactions can be done easily and effectively. The research results show that warung 3 brothers has recorded a report financein accordance with financial accounting standards and generate information needed to be faster, more accurate and moreefficient in presenting reports.